Collaborative Virtual Environment System for Distance Education in Mathematics - Shatokhin, Evgeny (2004)
Distance Education today is available in most countries of the world. After appearance of Internet distance education became more available and convenient because Internet is known as the largest information network and nowadays Internet is present almost in every home. Forms of Distance education can be categorized as: asynchronous and synchronous. Synchronous distance education environment can be virtual class or other virtual environment (e.g. online chat, video conferencing) where educator and educated communicate in real time. Asynchronous - email, web forum.Research presented in this thesis focuses in synchronous distance education in mathematics. The main question studied in this research is how to design learning environment for distance education in mathematics. To address this question such research areas as Computer Supported Collaborative Learning (CSCL) and some other related works are studied. CSCL is related how group of people separated by distance can learn in virtual environment collaboratively. Based on the best practices of CSCL and related works in area of distance education in mathematics, we developed concepts and presented a way which can be used to design an environment for distance education in mathematics. Designed environment is used to develop software prototype.Software prototype developed in this project named SynDiMath which is stands for Synchronous Distance Mathematics. It allows synchronous collaboration through Internet of group of participants and teachers by giving them right to use shared resources such as workspace for writing Mathematical formulas, whiteboard for drawing and fast sketching of problem, chat and computational engine. Mathematica software developed by Wolfram Research (Mathematica 5.0, 2003) is used as computational engine. Developed software allows each client (student) to have two separate workspaces. First workspace called "groupspace" where group of students together with teacher may discuss Mathematical ideas and solve problems. Second is a personal workspace called "notepad" where student may work on personal assignments and have one to one discussion with teacher. Discussion can be saved as step-by-step history and reused in future with other group of students or single student as a lesson or tutorial. Alternatively content of discussion can be saved in Hypertext Markup Language (HTML). In case of HTML content is static web page that can be included into website.